2021
DOI: 10.1055/s-0041-1726461
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Cephalexin in COVID-19 Treatment Combinations May Prevent Lung Involvement in Mild Infections: A Case Report with Pharmacological Genomics Perspective

Abstract: Novel coronavirus disease 2019 (COVID-19) is caused by a nonsegmented positive sense RNA, enveloped RNA virus that belongs to the family of β-coronaviridae. This virus shall cause acute respiratory distress syndrome (ARDS) which consequently leads to breathing difficulty and need to admit to intensive care units (ICUs). The current conventional treatment combination in most of the hospitals in Iran includes azithromycin 500 + naproxen 500 + vitamin C 1,000 + Zinc + vitamin D3 1,000. In this case reports (n = 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…BSs are well-known for their emulsifying role in vaccines or drugs and would be extremely successful as they are from sustainable and natural sources with non-pyrogenic and non-toxic immunological adjuvants when combined with SARS-CoV-2 antigen for treatment. Consequently, this expresses that B. subtilis plays a key role as an immunosuppressive agent and shall be particularly deployed as an alternative/complementary therapy alongside current conventional therapies to ease SARS-Cov-2-associated inflammatory responses (Khodavirdipour, 2021).…”
Section: Surfactin Anti-inflammatory Role Against Sars-cov-2mentioning
confidence: 99%
“…BSs are well-known for their emulsifying role in vaccines or drugs and would be extremely successful as they are from sustainable and natural sources with non-pyrogenic and non-toxic immunological adjuvants when combined with SARS-CoV-2 antigen for treatment. Consequently, this expresses that B. subtilis plays a key role as an immunosuppressive agent and shall be particularly deployed as an alternative/complementary therapy alongside current conventional therapies to ease SARS-Cov-2-associated inflammatory responses (Khodavirdipour, 2021).…”
Section: Surfactin Anti-inflammatory Role Against Sars-cov-2mentioning
confidence: 99%
“…In contrast to placebo, it considerably declined period of symptoms of common cold, from 7.6 to 4.4 days. In the case study, it was observed that the combination of azithromycin (500) + naproxen (500) + vitamin C (1000) + zinc + vitamin D 3 (1000) resulted in significant outcomes in course of COVID-19 treatment (Khodavirdipour 2021 ) .…”
Section: Immune Fuctions Of Nutrientsmentioning
confidence: 99%
“…COVID-19 is a public health emergency with the fastest transmission speed, the broadest range of infection, and the most challenging prevention and control in the past 100 years ( Ye et al, 2020a , 2021 ; Chen et al, 2021 ; Tian et al, 2021a , b ; Han and Ye, 2022 ; Zhang et al, 2022 ), and it can cause multiple organ damage or even death ( Tian and Ye, 2020 ; Ye et al, 2020a , b , c ; Han and Ye, 2021 ; Han et al, 2021 ; Khodavirdipour et al, 2021a , b ; Tian et al, 2021b ). Vaccines and drugs are being developed ( Khodavirdipour et al, 2020 , 2021c , 2022 ; Khodavirdipour, 2021 ). In the past, it was considered that the airborne transmission of SARS-CoV-2 was the dominant route of transmission ( Jarvis, 2020 ).…”
Section: Introductionmentioning
confidence: 99%